Interação de moléculas sintéticas anfifílicas catiônicas com modelos miméticos de biomembranas - Almeida, Marcio Moreira de [UNIFESP] (2018)
Bacterial infections represent a serious health problem, aggravated by the resistance of these microorganisms to conventional antibiotic agents. Therefore, alternative treatments, such as those based on antimicrobial peptides and synthetic molecules with similar characteristics, have been recently sought. Antimicrobial peptides are amphiphilic and cationic molecules present in the immune system of plants and animals that cause the death of microorganisms through the destruction of their membrane. In this work, two classes of synthetic cationic amphiphilic molecules with possible antimicrobial action were studied. These molecules consist of two hydrocarbon chains and two ammonium groups, located at the ends of the hydrophobic chains (Bolalike) or polar region of the molecule (Geminilike). In addition, different lengths of amphiphilic hydrocarbon chains were tested. The molecules studied were B7, B11, G7 and G11, where the letter identifies the class (Bola or Gemini) and the numbers the length of the acyl chain. To understand the mechanism of action of these molecules, membrane mimetic models were used: large (LUVs) and giant (GUVs) unilamellar vesicles composed of POPC, a zwitterionic lipid, and POPG, an anionic lipid. The composition of POPC:POPG 7:3 was chosen to mimic bacterial membranes, whereas pure POPC bilayers were used as biomimetic model of eukaryotic membranes. Different techniques were used to evaluate the interaction between the amphiphilic molecules and the LUVs: isothermal titration calorimetry (ITC), to obtain information about the thermodynamics of the interaction, dynamic scattering (DLS) and zeta potential of the vesicles to measure the size and surface charge of the vesicles as the cationic molecules were added, and leakage assays of a fluorescence probe encapsulated in the LUVs to quantify the lytic activity of the molecules. In addition, GUV optical microscopy experiments were performed to visualize the effects caused by amphiphilic molecules on the membrane. The results show that both the hydrophilic and hydrophobic balance of the molecules and the positions of the charges (Bola or Gemini) have an effect on the activity and mechanism of action of these molecules. Geminilike molecules showed greater affinity for the membrane, but this affinity did not result in a considerable membrane permeabilization. On the other hand, even though Bolalike molecules did not exhibit such high membrane affinity, they caused considerable membrane permeabilization. Among the amphiphilic molecules tested, the molecule B11 presented a lytic activity comparable to that of antimicrobial peptides and is, therefore, the most promising molecule as a possible antimicrobial agent.